Battery

By optimizing the structural design of the electrode sheet and the isolation film in the lithium-ion battery, the glue between the first electrode sheet and the isolation film is ensured to be sufficient, and the problems of softening the battery cell and poor impregnation of the electrolyte are solved, and the circulation of the battery is improved Performance and preparation efficiency.

CN222233693UActive Publication Date: 2024-12-24ZHEJIANG COSMX BATTERY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202420492706.3
Authority / Receiving Office
CN · China
Patent Type
Utility models(China)
Current Assignee / Owner
Filing Date
2024-03-14
Publication Date
2024-12-24
Estimated Expiration
2034-03-14

AI Technical Summary

Technical Problem

Improper thickness of the lithium-ion battery isolation film glue layer leads to softening of the battery cell, poor infiltration of the electrolyte, and large ion transmission resistance, which affects the battery circulation performance and preparation efficiency.

Method used

The coating thickness ratio of the first electrode sheet and the second electrode sheet is designed to be 1.5 to 3:1, the thickness of the first glue layer is greater than the second glue layer, the first glue layer is filled in the depression area of ​​the first electrode sheet, and the second glue is The layer is filled in the recessed area of ​​the second electrode sheet to ensure sufficient glue between the first electrode sheet and the isolation film, and reduce the resistance of the isolation film to the electrolyte and ions.

Benefits of technology

It improves the hardness of the battery cell and the cycling performance of the battery, reduces material costs, shortens the battery preparation time, and improves the battery's energy density and charging and discharging performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN222233693U_ABST
    Figure CN222233693U_ABST
Patent Text Reader

Abstract

The utility model provides a battery, which comprises a first pole piece, a second pole piece and a third pole piece, the second pole piece comprises a second coating, and the thickness of the first coating is greater than that of the second coating; the isolating membrane is located between the first pole piece and the second pole piece, the isolating membrane comprises a base material layer, a first adhesive layer connected with the first coating and a second adhesive layer connected with the second coating, and the thickness of the first adhesive layer is larger than that of the second adhesive layer. According to the utility model, under the conditions of improving the wettability of electrolyte to the battery cell, reducing the transmission resistance of the isolating membrane to ions and improving the cycle performance of the battery, the softening phenomenon of the battery cell is improved, and the preparation efficiency and the yield of the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The utility model relates to the field of electrochemical energy storage devices, in particular to a battery. Background Art

[0002] Lithium-ion batteries are used in mobile consumer products, electric vehicles, power tools, energy storage and other fields due to their high operating voltage and energy density, low self-discharge level, long cycle life and no memory effect. The separator is an important component of lithium-ion batteries, which is used to separate the positive and negative electrodes and prevent battery short circuits, and has an important impact on battery performance.

[0003] Specifically, in battery products such as lithium-ion batteries, a substrate plus glue type isolation membrane (or diaphragm) is often used, that is, the isolation membrane includes a substrate and a glue layer coated on the surface of the substrate, and the positive electrode sheet, the isolation membrane and the negative electrode sheet are bonded together by hot pressing. Among them, the glue layer is usually coated on both surfaces of the substrate in a full coating manner (that is, each surface of the base layer is covered with the glue layer).

[0004] However, when the thickness of the glue layer on the surface of the separator is small, the adhesion between the separator and the positive and negative electrodes is poor or even unable to adhere, causing the battery cell formed by the positive electrode, separator and negative electrode to become soft and collapse at the end (especially the laminated battery cell is more prone to softening and collapse at the end). This can easily cause interference between the battery cell and the battery manufacturing equipment during the battery manufacturing process, affecting the battery preparation efficiency and yield. When the thickness of the glue layer on the surface of the separator is large, it will affect the wettability of the electrolyte and the transmission capacity of lithium ions, and increase the material cost. Specifically, the electrolyte can usually only pass through the separator. The micropores of the substrate and the glue layer are slowly infiltrated. If the thickness of the glue layer is too thick, there will be a lack of sufficient space between the isolation membrane and the positive and negative electrodes to store and infiltrate the electrolyte, resulting in insufficient battery liquid retention, and will increase the lithium ion transmission resistance, affecting the battery cycle performance. At the same time, a thick glue layer will make the infiltration (diffusion) resistance of the electrolyte in the battery cell larger, which will prolong the aging and infiltration time after injection (in the battery manufacturing process, after injection, aging and infiltration are required to allow the electrolyte to fully infiltrate the battery cell before formation), affecting the battery preparation efficiency. At the same time, a thick glue layer will also increase the material cost of the isolation membrane.

[0005] Therefore, how to improve the softening phenomenon of battery cells and improve the preparation efficiency and yield of batteries while improving the wettability of the electrolyte to the battery cells and reducing the transmission resistance of the isolation membrane to ions and improving the cycle performance of the battery remains a technical problem that needs to be urgently solved by technical personnel in this field. Utility Model Content

[0006] The utility model provides a battery, which can improve the softening phenomenon of the battery cell, improve the preparation efficiency and yield of the battery, and effectively overcome the defects of the prior art while improving the wettability of the electrolyte to the battery cell and reducing the transmission resistance of the isolation membrane to ions and improving the cycle performance of the battery.

[0007] The utility model provides a battery, comprising: a first pole piece, comprising a first coating; a second pole piece, comprising a second coating, the thickness of the first coating being greater than the thickness of the second coating; an isolation film, located between the first pole piece and the second pole piece, the isolation film comprising a substrate layer, a first adhesive layer connected to the first coating, and a second adhesive layer connected to the second coating, the thickness of the first adhesive layer being greater than the thickness of the second adhesive layer.

[0008] According to one embodiment of the present invention, the ratio of the thickness of the first adhesive layer to the thickness of the second adhesive layer is 1.8-3.5; and / or the thickness of the first adhesive layer is 800nm-1300nm; and / or the thickness of the second adhesive layer is 300nm-700nm.

[0009] According to one embodiment of the present invention, the ratio of the thickness of the first coating layer to the thickness of the second coating layer is (1.5-3):1.

[0010] According to one embodiment of the present invention, the thickness H of the first adhesive layer is 301 The thickness of the first coating H 101 Satisfaction: H 301 =800+a×(H 101 -72), 120≤a≤130, wherein the thickness H of the first adhesive layer 301 The unit is nm, the thickness H of the first coating 101 The unit is μm; and / or, the thickness H of the second adhesive layer 302 The thickness of the first coating H 101 Satisfaction: H 302 =300+b×(H 101 -72), 95≤b≤105, wherein the thickness of the second adhesive layer H 302 The unit is nm, the thickness H of the first coating 101 The unit is μm; and / or, the thickness H of the first coating layer 101 and the surface density of the first coating ρ 101 Satisfy 0.4≤H 101 / ρ 101 ≤0.5, wherein the thickness H of the first coating 101 The unit is μm, the surface density ρ of the first coating 101 The unit is g / m 2and / or the thickness of the first coating is 72 μm to 76 μm; and / or the surface density of the first coating is 161 to 170 g / m 2 .

[0011] According to one embodiment of the present utility model, the peeling force between the first pole piece and the isolation film is greater than the peeling force between the second pole piece and the isolation film; preferably, the peeling force F1 between the first pole piece and the isolation film and the peeling force F2 between the second pole piece and the isolation film satisfy: 1N / m<F1 / F2≤6N / m; preferably, the peeling force F1 between the first pole piece and the isolation film satisfies: 6N / m<F1<14N / m; preferably, the peeling force F2 between the second pole piece and the isolation film satisfies: 2.5N / m≤F2≤5N / m.

[0012] According to an embodiment of the present invention, the surface of the first coating layer facing the isolation film includes a first recessed area, and the first adhesive layer fills at least a portion of the first recessed area.

[0013] According to an embodiment of the present invention, the surface of the second coating layer facing the isolation film includes a second recessed area, and the second adhesive layer fills at least a portion of the second recessed area.

[0014] According to one embodiment of the present invention, the first pole piece is a positive pole piece, and the second pole piece is a negative pole piece.

[0015] According to one embodiment of the present invention, the thickness of the substrate layer is 9 μm to 16 μm.

[0016] According to one embodiment of the utility model, the battery includes a plurality of first pole sheets and a plurality of second pole sheets arranged in a stacked manner, and the plurality of first pole sheets and the plurality of second pole sheets are arranged in an alternating manner, and the first pole sheets and the second pole sheets are separated by the isolation membrane; or, in the battery, the first pole sheet includes a plurality of first straight portions, and a first bent portion connected between every two adjacent first straight portions, the second pole sheet includes a plurality of second straight portions, and a second bent portion connected between every two adjacent second straight portions, the plurality of first straight portions and the plurality of second straight portions are arranged in an alternating manner, and the first straight portions and the second straight portions are separated by the isolation membrane.

[0017] The battery provided by the utility model comprises a first pole piece, a second pole piece, and an isolating film located between the first pole piece and the second pole piece, wherein the thickness of the first coating of the first pole piece is greater than the thickness of the second coating of the second pole piece, and the thickness of the first adhesive layer on the side of the isolating film facing the first pole piece is greater than the thickness of the second adhesive layer on the side of the isolating film facing the second pole piece, so that more adhesive can be ensured between the first pole piece and the isolating film, the bonding force between the two can be improved, and the hardness of the battery cell can be improved, and the phenomenon of softening of the battery cell, collapse of the end and the like, as well as the interference between the battery cell and the equipment during the preparation process of the battery caused by the above, thereby affecting the preparation efficiency and yield of the battery, etc.; at the same time, the second coating of the second pole piece is thinner, and its adaptability is relatively good. A thin second adhesive layer can prevent the overall thickness of the adhesive layer on the surface of the isolation membrane from being too thick, thereby achieving the following effects: (1) reducing the resistance of the isolation membrane to the infiltration (diffusion) of the electrolyte in the battery cell, which is beneficial to the infiltration of the electrolyte into the battery cell, thereby reducing the aging infiltration time after liquid injection in the battery manufacturing process, improving the battery manufacturing efficiency, and at the same time increasing the battery's liquid retention capacity to ensure the long-term cycle performance of the battery; (2) reducing the isolation membrane's resistance to ion transmission (diffusion), increasing the ion diffusion rate, and improving the battery's charge and discharge performance; (3) reducing the thickness of the battery cell, increasing the battery's energy density, and providing more space for battery design; (4) reducing the amount of adhesive used to form the first adhesive layer and the second adhesive layer, thereby reducing material costs.

[0018] Therefore, in the utility model, combined with the thickness of the first coating of the first pole piece, the thickness of the second coating of the second pole piece, and the isolation membrane structure design (in the isolation membrane, the thickness of the first adhesive layer connected to the thicker first coating layer is thicker, and the thickness of the second adhesive layer connected to the thinner second coating layer is thinner), the wettability of the electrolyte to the battery cell can be improved, the ion transmission resistance can be reduced, the cycle performance and charge and discharge performance of the battery can be improved, and at the same time the energy density of the battery can be improved and the cost can be reduced. It can also take into account improving the hardness of the battery cell, improving the softening phenomenon of the battery cell, and improving the preparation efficiency and yield of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 is a scanning electron microscope image of the isolation film of Example 1;

[0020] Figure 2 It is a schematic diagram of the structure of the first pole piece, the isolation film and the second pole piece after hot pressing (an enlarged view of a part of the battery cell);

[0021] Figure 3 A schematic diagram showing the hardness of a battery cell;

[0022] Figure 4 Schematic diagram of the interface structure between the first coating and the isolation film in the battery cell;

[0023] Figure 51 is a cycle curve diagram of the battery of Example 1 and Comparative Example 1;

[0024] Figure 6 This is a schematic structural diagram of a laminated battery cell according to an embodiment of the utility model;

[0025] Figure 7 The figure is a schematic structural diagram of a wound battery cell according to an embodiment of the present invention.

[0026] Description of reference numerals:

[0027] 1: first pole piece; 11: first straight portion; 12: first bend portion; 100: first recessed area; 101: first coating layer; 102: first current collector; 2: second pole piece; 21: second straight portion; 22: second bend portion; 201: second coating layer; 202: second current collector; 3: isolation film; 301: first adhesive layer; 302: second adhesive layer; 303: substrate layer; 31: isolation layer; 32: third bend portion; 4: battery cell; 5: support structure; H 101 : The thickness of the first coating; H 301 : The thickness of the first adhesive layer; H 302 : The thickness of the second adhesive layer; H 303 : thickness of the substrate layer; H 201 : The thickness of the second coating. DETAILED DESCRIPTION

[0028] In order to enable those skilled in the art to better understand the scheme of the utility model, the utility model is further described in detail below. The specific implementation methods listed below are only for describing the principles and features of the utility model. The examples are only used to explain the utility model and do not limit the scope of the utility model. Based on the embodiments of the utility model, all other implementation methods obtained by ordinary technicians in this field without making creative work are within the scope of protection of the utility model.

[0029] The utility model embodiment provides a battery, such as Figure 1 , Figure 2 and Figure 6 As shown, the battery comprises: a first pole piece 1, comprising a first coating 101; a second pole piece 2, comprising a second coating 201, and the thickness of the first coating 101 is H 101 Greater than the thickness H of the second coating 201 201 ; The isolation film 3 is located between the first pole piece 1 and the second pole piece 2. The isolation film 3 includes a substrate layer 303, a first adhesive layer 301 connected to the first coating 101, and a second adhesive layer 302 connected to the second coating 201; the thickness H of the first adhesive layer 301 301 Greater than the thickness H of the second adhesive layer 302 302 .

[0030] Specifically, the battery includes a battery cell 4 , and the battery cell 4 includes a first pole piece 1 , a second pole piece 2 , and a separation film 3 spaced between the first pole piece 1 and the second pole piece 2 .

[0031] In the above battery, the thickness H of the first coating 101 of the first electrode 1 is 101 Greater than the thickness of the second coating 201 of the second pole piece 2 201 , and simultaneously coordinately control the thickness H of the first adhesive layer 301 on the side of the isolation film 3 facing the first pole piece 1 301 is greater than the thickness H of the second adhesive layer 302 on the side of the isolation film 3 facing the second pole piece 2 302 In this way, the hardness of the battery cell 4 can be improved, and the battery cell 4 can be prevented from becoming soft, collapsing at the end, and interfering with the equipment during the battery preparation process, thereby affecting the battery preparation efficiency and yield. At the same time, it can also prevent the overall thickness of the adhesive layer on the surface of the isolation membrane 3 from being too thick, and can have the following effects: (1) reducing the resistance of the isolation membrane 3 to the infiltration (diffusion) of the electrolyte in the battery cell 4, which is beneficial to the infiltration of the electrolyte into the battery cell 4, thereby reducing the aging and infiltration time after the injection in the battery preparation process, and improving the battery preparation efficiency. (1) reduce the transmission (diffusion) resistance of the isolation membrane 3 to ions, increase the ion diffusion rate, and improve the battery charging and discharging performance; (2) reduce the thickness of the battery cell 4, increase the energy density of the battery, and provide more space for battery design; (3) reduce the amount of glue used to form the first glue layer 301 and the second glue layer 302, and reduce material costs; (4) maintain a large energy density and capacity of the battery cell 4 (under the same battery cell 4 thickness, too thick a glue layer will reduce the capacity of the battery cell 4).

[0032] According to the inventor's research, the thickness H of the first coating layer 101 is 101 Greater than the thickness H of the second coating 201 201 , accordingly, the thickness of the first pole piece 1 is greater than the thickness of the second pole piece 2, the weight of the first pole piece 1 is greater than the weight of the second pole piece 2, and the first pole piece 1 has a higher strength than the second pole piece 2. Therefore, the first pole piece 1 occupies a larger proportion in the battery cell 4, and the hardness of the battery cell 4 is mainly affected by the first pole piece 1. In the embodiment of the utility model, by making the first adhesive layer 301 on the side of the isolation film 3 facing the first pole piece 1 have a greater thickness, the amount of adhesive between the first pole piece 1 and the isolation film 3 is increased, thereby improving the adhesion between the first pole piece 1 and the isolation film 3, and then improving the hardness of the battery cell 4, avoiding the softening phenomenon of the battery cell 4, and the resulting collapse of the end of the battery cell 4 and interference with the battery manufacturing equipment, etc., thereby facilitating the normal production of the battery and improving the preparation efficiency and yield of the battery.

[0033] At the same time, the weight and strength of the second pole piece 2 are relatively small, so that the second glue layer 302 on the side of the isolation membrane 3 facing the second pole piece 2 has a relatively small thickness, which can reduce the overall glue amount of the isolation membrane 3 while maintaining good adhesion between the second pole piece 2 and the isolation membrane 3, which is not only beneficial to reducing the thickness of the battery cell 4 and improving the energy density of the battery, but also can improve the wettability of the electrolyte to the battery cell 4, reduce the aging and infiltration time after injection during the battery preparation process, and increase the battery liquid retention. At the same time, the lower glue amount on the isolation membrane 3 can also reduce the lithium ion transmission resistance, which is beneficial to the lithium ion deintercalation between the first and second electrodes during the battery cycle, and improves the long-term cycle performance.

[0034] Specifically, the thickness H of the first coating layer 101 is 101 The thickness H of the second coating 201 201 The ratio can be (1.5-3):1, for example, 1.5:1, 1.8:1, 2:1, 2.3:1, 2.5:1, 2.8:1, 3:1 or a range consisting of any two of them.

[0035] In addition, the thickness H of the first adhesive layer 301 is 301 The thickness H of the first coating 101 101 Satisfaction: H 301 =800+a×(H 101 -72), 120≤a≤130, a is, for example, 125, wherein the thickness H of the first adhesive layer 301 301 The unit is nm, and the thickness H of the first coating 101 is 101 The unit is μm, so when the thickness H of the first coating 101 101 When the thickness H of the first adhesive layer 301 is reduced or increased, the thickness H of the first adhesive layer 301 may be appropriately reduced or increased accordingly. 301 By controlling the relationship between the two within the above range, it is beneficial to further improve the adhesion between the first pole piece 1 and the isolation film 3, overcome the softening phenomenon of the battery cell, and at the same time avoid using too much glue to affect the electrolyte wettability and battery cell capacity and other performance.

[0036] For example, a=125, when the thickness H of the first coating 101 is 101 =72 μm, the thickness H of the first adhesive layer 301 301 = 800 nm, when the thickness H of the first coating 101 101 =76 μm, the thickness H of the first adhesive layer 301 301 =1300nm.

[0037] In addition, the thickness H of the second adhesive layer 302 is 302 The thickness H of the first coating 101 101 Satisfaction: H 302 =300+b×(H 101-72), 95≤b≤105, b is, for example, 100, wherein the thickness H of the second adhesive layer 302 302 The unit is nm, and the thickness H of the first coating 101 is 101 The unit is μm, which is beneficial to further improve the softening phenomenon of the battery cell, while avoiding excessive use of glue material to affect the electrolyte wettability and battery cell capacity and other performance.

[0038] Further considering the relationship between the thickness of the first adhesive layer 301 and the thickness of the first coating layer 101, and the influence of the two on the bonding force between the first electrode 1 and the isolation film 3 and the capacity of the battery cell 4, the thickness H of the first coating layer 101 can be further controlled. 101 and the surface density ρ of the first coating 101 101 Satisfy 0.4≤H 101 / ρ 101 ≤0.5, H 101 / ρ 101 For example, it is 0.45, wherein the thickness H of the first coating 101 101 The unit is μm, and the surface density ρ of the first coating 101 101 The unit is g / m 2 This is beneficial to further improve the performance of the battery cell 4, such as hardness and capacity.

[0039] In some embodiments, the thickness H of the first coating 101 is 101 The thickness may be in the range of 72 μm to 76 μm, for example, 72 μm, 73 μm, 74 μm, 75 μm, 76 μm or a range consisting of any two thereof.

[0040] In some embodiments, the surface density of the first coating 101 is 101 Can be 161~170g / m 2 , for example 161g / m 2 , 163g / m 2 , 165g / m 2 , 168g / m 2 , 170g / m 2 Or a range consisting of any two of them.

[0041] In the embodiment of the present invention, the surface density of the first coating 101 refers to the surface density of the first coating 101 on a single side of the first current collector 102, rather than the sum of the surface densities of the first coating 101 on the front and back sides of the first current collector 102. The surface density of the first coating 101 = the mass of the single-sided first coating 101 / the area of ​​the single-sided first coating 101. The area of ​​the single-sided first coating 101 is the surface area of ​​the first coating 101, which is also the area of ​​the projection of the first coating 101 on the first current collector 102.

[0042] In the embodiment of the present invention, the thickness of each coating or adhesive layer is also the thickness of a single side. Taking the thickness of the first coating 101 as an example, it is the thickness of the first coating 101 on a single side of the first current collector 102, rather than the sum of the thicknesses of the first coating 101 on both sides of the first current collector 102.

[0043] In addition, the thickness H of the first adhesive layer 301 is 301 The thickness H of the second adhesive layer 302 302 The ratio (H 301 / H 302 ) can be in the range of 1.8 to 3.5, for example, 1.8, 1.85, 1.9, 2, 2.1, 2.3, 2.6, 2.8, 3.1 or a range consisting of any two of them.

[0044] Specifically, the thickness H of the first adhesive layer 301 is 301 The thickness H of the second adhesive layer 302 302 The difference can be 100nm to 1000nm, for example, 100nm, 300nm, 500nm, 700nm, 850nm, 1000nm or a range consisting of any two of them. This is conducive to further improving the softening problem of the battery cell 4 and the wettability of the electrolyte to the battery cell 4, and further improving the preparation efficiency and yield of the battery, as well as the cycle performance of the battery.

[0045] In some embodiments, the thickness H of the first adhesive layer 301 is 301 It can be 800nm ​​to 1300nm, for example, 800nm, 900nm, 1000nm, 1100nm, 1200nm, 1300nm or a range consisting of any two of them. This is beneficial to improving the adhesion between the first pole piece 1 and the isolation membrane 3, while improving the wettability of the electrolyte to the battery cell 4, thereby improving the cycle performance of the battery.

[0046] In some embodiments, the thickness H of the second adhesive layer 302 is 302 It is 300nm to 700nm, for example, 300nm, 400nm, 500nm, 600nm, 700nm or a range composed of any two of them. This is beneficial to improving the adhesion between the second pole piece 2 and the isolation membrane 3, while improving the wettability of the electrolyte to the battery cell 4, thereby improving the cycle performance of the battery.

[0047] In the embodiment of the utility model, the first coating 101 of the first pole piece 1 and the first adhesive layer 301 of the isolation film 3 are bonded, so that the first pole piece 1 and the isolation film 3 are bonded, and the second coating 201 of the second pole piece 2 and the second adhesive layer 302 of the isolation film 3 are bonded, so that the second pole piece 2 and the isolation film 3 are bonded, and the bonding force between the first pole piece 1 and the isolation film 3 may be greater than the bonding force between the second pole piece 2 and the isolation film 3, that is, the peeling force F1 between the first pole piece 1 and the isolation film 3 may be greater than the peeling force F2 between the second pole piece 2 and the isolation film 3.

[0048] Specifically, the peeling force F1 between the first pole piece 1 and the isolation film 3, and the peeling force F2 between the second pole piece 2 and the isolation film 3 can satisfy: 1N / m<F1 / F2≤6N / m, and F1 / F2 is, for example, 1.1N / m, 1.5N / m, 2N / m, 2.3N / m, 2.5N / m, 2.8N / m, 3N / m, 3.3N / m, 3.5N / m, 4N / m, 4.5N / m, 5N / m, 5.5N / m, 6N / m or a range consisting of any two of them.

[0049] In addition, the peeling force F1 between the first pole piece 1 and the isolation film 3 and the peeling force F2 between the second pole piece 2 and the isolation film 3 can satisfy 1N / m<F1-F2<11.5N / m, and F1-F2 is, for example, 1.5N / m, 2N / m, 3N / m, 4N / m, 5N / m, 6N / m, 7N / m, 8N / m, 9N / m, 10N / m, 11N / m or a range consisting of any two of them.

[0050] Specifically, the peeling force F1 between the first pole piece 1 and the isolation film 3 can satisfy: 6N / m<F1<14N / m, where F1 is, for example, 6.5N / m, 7N / m, 8N / m, 9N / m, 10N / m, 11N / m, 12N / m, 13N / m, 13.5N / m or a range consisting of any two of them.

[0051] Specifically, the peeling force F2 between the second pole piece 2 and the isolation film 3 can satisfy: 2.5N / m≤F2≤5N / m, where F2 is, for example, 2.5N / m, 3N / m, 3.5N / m, 4N / m, 4.5N / m, 5N / m or a range consisting of any two of them.

[0052] In the embodiment of the utility model, the peeling force is the 180° peeling force measured by the 180° peeling force test. The peeling force F1 between the first electrode 1 and the isolation film 3 and the peeling force F2 between the second electrode 2 and the isolation film 3 can be measured by a conventional tensile testing machine in the art. The peeling force F1 between the first electrode 1 and the isolation film 3 and the peeling force F2 between the second electrode 2 and the isolation film 3 both represent the peeling force per unit length (i.e., the tensile force used to peel off the electrode and the isolation film of unit length using a tensile testing machine). The testing process may specifically include: (1) disassembling the battery in a dry environment and taking out the battery cell; (2) removing the composite structure in which the electrode and the isolation film 3 are bonded together from the battery cell, and cutting the composite structure into a test pattern, for example, cutting it into a test pattern with a width w of 20 mm and a length L of 50 mm; (3) maintaining the original positions of the electrode and the isolation film 3 in the test pattern. , the test sample is hot pressed for 10s at a temperature of 90°C and a pressure of 0.6Mpa (after cutting, the adhesion between the electrode and the isolation membrane 3 will weaken or even peel off, so after the hot pressing in step (3), the test in step (4) is carried out); (4) after the hot pressing is completed, the test sample is placed on a tensile testing machine for testing, and the peeling force F between the electrode and the isolation membrane 3 is measured; wherein, during the test, the electrode and the isolation membrane 3 in the test sample are pulled and peeled by the tensile testing machine, and the test part is the wide side of one side of the test sample in the width direction (the wide side of the electrode and the wide side of the isolation membrane 3 are covered by the tensile testing machine, that is, both are subjected to tension), and the maximum tension in the peeling process (usually the tension corresponding to the initial separation between the electrode and the isolation membrane 3) is measured as F0, and then the peeling force F between the electrode and the isolation membrane 3 can be obtained according to F=F0 / w.

[0053] Among them, when testing the peeling force F1 between the first electrode 1 and the isolation film 3, the electrode in steps (1) to (4) is the first electrode 1, and F in step (4) is F1 (i.e., F1 = F0 / w); when testing the peeling force F2 between the second electrode 2 and the isolation film 3, the electrode in steps (1) to (4) is the second electrode 2, and F in step (4) is F2 (i.e., F2 = F0 / w).

[0054] Generally, the first pole piece 1 includes a first current collector 102 and a first coating 101 disposed on the surface of the first current collector 102 . The first current collector 102 has two opposite surfaces. Specifically, the first coating 101 may be disposed on both opposite surfaces of the first current collector 102 .

[0055] The first coating layer 101 may include a first active material layer, and the first active material layer generally includes materials such as a first active material, a conductive agent, and a binder.

[0056] In addition, the second pole piece 2 includes a second current collector 202 and a second coating 201 disposed on the surface of the second current collector 202 . The second current collector 202 has two opposite surfaces. Specifically, the first coating 101 may be disposed on both opposite surfaces of the second current collector 202 .

[0057] The second coating layer 201 may include a second active material layer, and the second active material layer generally includes materials such as a second active material, a conductive agent, and a binder.

[0058] Specifically, the polarities of the first electrode sheet 1 and the second electrode sheet 2 are opposite. For example, the first electrode sheet 1 is a positive electrode sheet, the second electrode sheet 2 is a negative electrode sheet, and accordingly, the first current collector 102 is a positive electrode current collector, the first coating 101 is a positive electrode coating, the first active material layer is a positive electrode active material layer, the first active material is a positive electrode active material, the second current collector 202 is a negative electrode current collector, the second coating 201 is a negative electrode coating, the second active material layer is a negative electrode active material layer, and the second active material is a negative electrode active material. Alternatively, the first electrode sheet 1 is a negative electrode sheet, the second electrode sheet 2 is a positive electrode sheet, and accordingly, the first current collector 102 is a negative electrode current collector, the first coating 101 is a negative electrode coating, the first active material layer is a negative electrode active material layer, the first active material is a negative electrode active material, the second current collector 202 is a positive electrode current collector, the second coating 201 is a positive electrode coating, the second active material layer is a positive electrode active material layer, and the second active material is a positive electrode active material.

[0059] According to the inventor's further research, due to factors such as the properties of the positive and negative electrode materials, the positive electrode sheet and the separator 3 are more likely to have problems such as insufficient glue and poor adhesion, which will seriously affect the hardness and other properties of the battery cell, and easily cause the battery cell to become soft and collapse at the end. For example, the main factors affecting the poor adhesion between the positive electrode sheet and the separator 3 are: (1) Compared with the negative electrode sheet, the active material coated on the positive electrode sheet (i.e., the positive electrode coating material) is usually a particle with a larger particle size, which makes the surface porosity of the positive electrode sheet larger and has a larger surface density. Therefore, if the amount of glue between the positive electrode sheet and the separator 3 is insufficient, the glue material is not easy to penetrate into the pores, which makes the adhesion between the separator 3 and the positive electrode sheet smaller; (2) At the same time, since the positive electrode sheet and the negative electrode sheet need to cooperate in terms of capacity and NP ratio (negative electrode sheet capacity / positive electrode sheet capacity) (for example, if the positive electrode sheet capacity is Too large, which easily leads to lithium precipitation problems), therefore, the positive electrode active material coated on the positive electrode sheet is usually thicker than the negative electrode active material coated on the negative electrode sheet (that is, the thickness of the positive electrode coating is usually greater than the thickness of the negative electrode coating). In this case, if the glue content between the positive electrode sheet and the isolation film 3 is the same as the glue content between the negative electrode sheet and the isolation film 3, the adhesion between the positive electrode sheet and the isolation film 3 is poor. For example, the adhesion between the positive electrode sheet and the isolation film 3 will be less than the adhesion between the negative electrode sheet and the isolation film 3. The poor adhesion between the thicker positive electrode sheet and the isolation film 3 will make the battery cell hardness low, which is easy to cause the battery cell to soften. Therefore, in the embodiment of the utility model, it is preferred that the first electrode sheet 1 is the positive electrode sheet and the second electrode sheet 2 is the negative electrode sheet. In this way, the thickness of the first glue layer 301 between the positive electrode sheet and the isolation film 3 is thicker, so that there is more glue content between the positive electrode sheet and the isolation film 3, which is conducive to improving the adhesion between the positive electrode sheet and the isolation film 3, and effectively improving the problem of battery cell softening.

[0060] In the embodiment of the utility model, the positive electrode current collector may include aluminum foil or other conventional positive electrode current collectors in the art, and the negative electrode current collector may include copper foil or other conventional negative electrode current collectors in the art, without particular limitation.

[0061] In an embodiment of the utility model, the positive electrode active material may include conventional positive electrode active materials in the art, for example, lithium-containing active materials, such as lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, ternary materials, lithium iron phosphate, lithium manganese iron phosphate, lithium vanadium phosphate, lithium vanadium phosphate, and at least one of lithium-rich manganese-based materials. The ternary material may include lithium nickel cobalt manganese oxide and / or lithium nickel cobalt aluminum oxide, etc.

[0062] In an embodiment of the utility model, the negative electrode active material layer may include a negative electrode active material, a conductive agent, a binder and a thickener. The negative electrode active material may include conventional negative electrode active materials in the art, such as graphite, mesophase carbon microbeads, soft carbon, hard carbon, silicon material, silicon oxygen material, silicon carbon material, and one or more of lithium titanate.

[0063] In an embodiment of the utility model, the conductive agent in the first pole piece 1 and the second pole piece 2 can be a conventional conductive material in the art, for example, one or more of carbon black (SP), acetylene black, carbon nanotubes, conductive graphite, and graphene; the binder can be a conventional binder in the art, for example, one or more of polyvinylidene fluoride (PVDF), a copolymer of vinylidene fluoride and hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylic acid salt, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene, polyhexafluoropropylene, and styrene-butadiene rubber (SBR); the thickener can be a conventional thickening material in the art, for example, sodium carboxymethyl cellulose (CMC-Na), etc.

[0064] In general, if Figure 4 As shown, the surface of the first coating 101 facing the isolation film 3 includes a first recessed area 100 , and the first adhesive layer 301 fills at least a portion (partial or entire) of the first recessed area 100 .

[0065] Specifically, the surface of the first coating 101 is a porous structure, that is, it includes a plurality of first recessed areas 100, which are distributed on the surface of the first coating 101, making the surface of the first coating 101 uneven. The first adhesive layer 301 is bonded to the surface of the first coating 101 and filled in at least part of the first recessed areas 100 on the surface, so that the first electrode 1 and the isolation film 3 have greater adhesion, further improving the hardness of the battery cell 4 and improving the softening phenomenon of the battery cell 4.

[0066] In addition, the surface of the second coating layer 201 facing the isolation film 3 includes a second recessed area, and the second adhesive layer 302 fills at least a portion (partial or entire) of the second recessed area.

[0067] Specifically, the surface of the second coating 201 is a porous structure, that is, it includes a plurality of second recessed areas, which are distributed on the surface of the second coating 201, making the surface of the second coating 201 uneven. The second adhesive layer 302 is bonded to the surface of the second coating 201 and filled in at least part of the second recessed area on the surface, so that the second electrode 2 and the isolation film 3 have greater adhesion, further improving the hardness of the battery cell 4 and improving the softening phenomenon of the battery cell 4.

[0068] Specifically, the first electrode sheet 1 and the second electrode sheet 2 can be prepared by conventional coating methods in the art. Taking the positive electrode sheet as an example, materials such as the positive electrode active material, the conductive agent and the binder can be placed in a solvent to prepare a positive electrode slurry. The solvent used includes, for example, N-methylpyrrolidone (NMP). The positive electrode slurry is then applied to the surface of the positive electrode collector. After drying, rolling and other processes, a positive electrode active material layer is formed on the surface of the collector to prepare a positive electrode sheet.

[0069] In addition, the battery cell 4 can be prepared through a hot pressing process, and its preparation process may specifically include: stacking the first pole piece 1, the isolation membrane 3 and the second pole piece 2 in sequence and then hot pressing them, so that the first pole piece 1 is bonded to the isolation membrane 3 through the first adhesive layer 301 of the isolation membrane 3, and the second pole piece 2 is bonded to the isolation membrane 3 through the second adhesive layer 302 of the isolation membrane 3. Thus, through the action of hot pressing, the first pole piece 1, the isolation membrane 3 and the second pole piece 2 are bonded together to form a stable battery cell 4 structure.

[0070] The embodiment of the utility model can be hot pressed by a hot press, and the hot pressing conditions can be: temperature of 85-95° C., such as 90° C., pressure of 0.5-0.7 MPa, such as 0.6 MPa, and hot pressing time of 8-12 s, such as 10 s.

[0071] Generally, after hot pressing, in the formed battery cell 4, the thickness of the first glue layer 301 and the second glue layer 302 of the isolation film 3 are substantially equal to the thickness before hot pressing (the change rate does not exceed 10%), and the thickness of the substrate layer 303 is also substantially equal to the thickness before hot pressing.

[0072] In the above preparation process, a porous structure (i.e., multiple first recessed areas 100) is formed on the surface of the first coating 101, and the first adhesive layer 301 fills at least a portion of the first recessed areas 100; a porous structure (i.e., multiple second recessed areas) is formed on the surface of the second coating 201, and the second adhesive layer 302 fills at least a portion of the second recessed areas.

[0073] In some embodiments, the first adhesive layer 301 may include a PVDF layer, that is, the material of the first adhesive layer 301 may be PVDF, that is, it is mainly formed of PVDF.

[0074] In some embodiments, the second adhesive layer 302 may include a PVDF layer, that is, the material of the second adhesive layer 302 may be PVDF, that is, it is mainly formed of PVDF.

[0075] Specifically, the molecular weight of the PVDF of the first adhesive layer may be equal to or greater than the molecular weight of the PVDF of the second adhesive layer. The molecular weight of the PVDF of the first adhesive layer may be 500,000 to 600,000, and the molecular weight of the PVDF of the second adhesive layer may be 300,000 to 600,000, for example, 300,000, 350,000, 400,000, 450,000, 500,000, 550,000, 600,000 or a range consisting of any two of them.

[0076] Generally, as the molecular weight of PVDF increases, its adhesive effect will be enhanced, therefore, PVDF with different molecular weights can be used to form the first adhesive layer 301 and the second adhesive layer 302, respectively, so as to further adjust the adhesive effect of the first adhesive layer 301 and the second adhesive layer 302. In some preferred embodiments, the molecular weight of the PVDF of the first adhesive layer 301 is greater than the molecular weight of the PVDF of the second adhesive layer 302, so that the viscosity of the first adhesive layer 301 is greater than the viscosity of the second adhesive layer 302.

[0077] In a specific implementation, the molecular weight of the PVDF in the first adhesive layer and the second adhesive layer can be measured by mass spectrometry.

[0078] Generally, PVDF is polymerized from vinylidene fluoride monomers, and the molecular weight of the synthesized PVDF can be controlled by regulating the polymerization reaction time and / or reaction temperature. For example, the molecular weight of the synthesized PVDF can be reduced by reducing the polymerization reaction time and / or reaction temperature to obtain low molecular weight PVDF. However, the embodiments of the present invention are not limited to this, and PVDF of corresponding molecular weight can also be obtained by other conventional methods.

[0079] In addition, the first adhesive layer 301 may also contain hexafluoropropylene (HFP) and / or styrene butadiene rubber (SBR), which is beneficial to improving the adhesion of the first adhesive layer 301 and enhancing the bonding force between the first adhesive layer 301 and the first pole piece 1 .

[0080] Generally, in the first adhesive layer 301, the content of HFP and SBR is small relative to that of PVDF, and the ratio of the sum of the mass of HFP and SBR to the mass of PVDF is generally less than or equal to 5:95.

[0081] In addition, the second adhesive layer 302 may also contain hexafluoropropylene (HFP) and / or styrene butadiene rubber (SBR), which is beneficial to improving the adhesion of the second adhesive layer 302 and enhancing the bonding force between the second adhesive layer 302 and the second pole piece 2 .

[0082] Generally, in the second adhesive layer 302, the content of HFP and SBR is small relative to that of PVDF, and the ratio of the sum of the mass of HFP and SBR to the mass of PVDF is generally less than or equal to 5:95.

[0083] In addition, the thickness H of the base material layer 303 is 303 The thickness may be in the range of 9 μm to 16 μm, for example, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm or a range consisting of any two thereof.

[0084] Specifically, the substrate layer 303 may include polypropylene and / or polyethylene, that is, the substrate layer 303 may include one or more of a polypropylene layer, a polyethylene layer, and a mixed layer of polypropylene and polyethylene (containing a mixture of polypropylene and polyethylene).

[0085] Specifically, the projection of the first adhesive layer 301 on the plane where the substrate layer 303 is located can cover the projection of the substrate layer 303 on the plane where the substrate layer 303 is located, and the two generally overlap, that is, the surface of the substrate layer 303 is fully coated to form the first adhesive layer 301.

[0086] In addition, the projection of the second adhesive layer 302 on the plane where the substrate layer 303 is located can cover the projection of the substrate layer 303 on the plane where the substrate layer 303 is located, and the two generally overlap, that is, the surface of the substrate layer 303 is fully coated to form the second adhesive layer 302.

[0087] For example, Figure 1 FIG. 1 is a scanning electron microscope (SEM) image of a cross section (the cross section is parallel to the thickness direction of the isolation film) of an isolation film 3 before hot pressing in an embodiment. It can be seen that the first adhesive layer 301 and the second adhesive layer 302 respectively cover the surfaces of the substrate layer 303 on the opposite sides in the thickness direction. The thickness H of the substrate layer 303 is 303 The thickness H of the first adhesive layer 301 is about 12.2 μm to 13.8 μm. 301 is about 1150nm (1.15μm), and the thickness H of the second glue layer 302 is 302 About 535μm.

[0088] In some embodiments, Figure 6 As shown, the above-mentioned battery cell 4 can be a stacked battery cell (stacked core), that is, the battery cell 4 includes a plurality of first pole sheets 1 and a plurality of second pole sheets 2 that are stacked, the plurality of first pole sheets 1 and the plurality of second pole sheets 2 are alternately arranged, and the first pole sheets 1 and the second pole sheets 2 are separated by the isolation membrane 3, that is, each first pole sheet 1 is separated from the second pole sheet 2 by the isolation membrane 3, and each second pole sheet 2 is separated from the first pole sheet 1 by the isolation membrane 3.

[0089] Continue to refer Figure 6 The isolation membrane 3 can be folded into a multi-layer folded structure, that is, the isolation membrane 3 includes multiple isolation layers 31, and a third bending portion 32 connected between every two adjacent isolation layers 31, each isolation layer 31 is spaced between the first pole piece 1 and the second pole piece 2, and the isolation membrane 3 is folded through the third bending portion 32 to form a multi-layer folded structure.

[0090] In a specific implementation, multiple first pole sheets 1, isolation membranes 3 and multiple second pole sheets 2 can be stacked in a preset order and then hot pressed to bond the first pole sheets 1, isolation membranes 3 and second pole sheets 2 together to form a stable stacked battery cell 4 structure.

[0091] In other embodiments, Figure 7 As shown, the above-mentioned battery cell 4 can be a wound battery cell 4 (wound core), that is, in the battery cell 4, the first pole piece 1 and the second pole piece 2 each have a wound structure, that is, the first pole piece 1 includes a plurality of first straight portions 11, and a first bent portion 12 connected between every two adjacent first straight portions 11, and the second pole piece includes a plurality of second straight portions 21, and a second bent portion 22 connected between every two adjacent second straight portions 21, the plurality of first straight portions 11 and the plurality of second straight portions 21 are stacked, and the plurality of first straight portions 11 and the plurality of second straight portions 21 are staggered, and the first straight portions 11 and the second straight portions 21 are separated by an isolation membrane 3.

[0092] In a specific implementation, the first pole piece 1, the isolation film 3 and the second pole piece 2 are stacked in sequence, and then hot pressed to bond the first pole piece 1, the isolation film 3 and the second pole piece 2 together, and then wound to form a winding core of a winding structure.

[0093] In addition, the battery further comprises a shell for encapsulating the battery cell 4, the shell encloses a cavity, and the battery cell 4 is located in the cavity to achieve encapsulation of the battery cell 4. The embodiment of the utility model can encapsulate the battery cell 4 using a conventional shell in the art, and the shell comprises, for example, a soft packaging film, such as an aluminum-plastic film.

[0094] In addition, the battery also includes an electrolyte. The embodiments of the present invention may use conventional electrolytes in the art, for example, the electrolyte is a non-aqueous electrolyte.

[0095] Specifically, the electrolyte may include a solvent, a lithium salt (solute) and an additive, the solvent may include an organic solvent, the organic solvent may include one or more of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), and ethyl propyl carbonate (EPC); the solute may include a lithium salt, the lithium salt may include one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), and lithium hexafluoroarsenate (LiAsF6); the additive may include one or more of vinylene carbonate (VC), vinyl ethylene carbonate (VEC), fluoroethylene carbonate (FEC), succinonitrile (SN), and adiponitrile (ADN).

[0096] In the embodiment of the utility model, the battery can be prepared by conventional methods in the field. For example, after the battery core 4 is packaged, an electrolyte is injected therein, and after aging and infiltration, the battery is formed and sealed again to obtain a battery. These steps / processes are conventional operations in the field, and the utility model does not impose any special restrictions on this and will not be repeated.

[0097] The present invention is further described below through specific embodiments.

[0098] Example 1

[0099] 1. Preparation of positive electrode

[0100] Lithium iron phosphate, carbon black and PVDF were mixed in a mass ratio of 96.5:1.4:2.1, and NMP was added thereto to prepare a positive electrode slurry;

[0101] The positive electrode slurry is coated on the front and back surfaces of the aluminum foil, and after drying and rolling, a positive electrode coating is formed on the front and back surfaces of the aluminum foil to prepare a positive electrode sheet; wherein the surface density of the positive electrode coating on one side is 166g / m 2 .

[0102] 2. Preparation of negative electrode sheet

[0103] Graphite, carbon black, SBR, and sodium carboxymethyl cellulose were mixed in a mass ratio of 95:2:1.8:1.2, and deionized water was added thereto to prepare a negative electrode slurry;

[0104] The negative electrode slurry is coated on the front and back surfaces of the copper foil, and after drying and rolling, a negative electrode coating is formed on the front and back surfaces of the copper foil to obtain a positive electrode sheet.

[0105] 3. Preparation of batteries

[0106] The positive electrode sheet, the separator and the negative electrode sheet are stacked and hot pressed to make the positive electrode coating of the positive electrode sheet and the first adhesive layer of the separator bonded, and the negative electrode coating of the negative electrode sheet and the second adhesive layer of the separator bonded, so as to assemble a stacked battery cell; wherein the hot pressing conditions are: temperature of 90° C., pressure of 0.6 MPa, and hot pressing time of 10 s;

[0107] The battery cell is encapsulated with aluminum-plastic film, and electrolyte is injected into it. After aging and infiltration, the formation and secondary sealing processes are carried out to obtain a lithium-ion battery.

[0108] The electrolyte is prepared by solvent, LiPF6 and VC in a mass ratio of 85:11:4, the solvent is EC and PC, and the mass ratio of EC and PC is 3:2.

[0109] Among them, the thickness of the battery cell (stacked core) is 9.68mm. In the battery cell, the positive electrode sheet is 32 layers, the negative electrode sheet is 33 layers, the isolation film is folded into 66 isolation layers, and the positive electrode sheet and the negative electrode sheet are separated by the isolation layer.

[0110] Among them, the isolation film includes a substrate layer, a first adhesive layer located on the side of the substrate layer facing the positive electrode sheet, and a second adhesive layer located on the side of the substrate layer facing the negative electrode sheet; the substrate layer is a polypropylene layer, the first adhesive layer is a PVDF layer, and the second adhesive layer is a PVDF layer. The molecular weight of the PVDF in the first adhesive layer is 550,000, and the molecular weight of the PVDF in the first adhesive layer is 550,000.

[0111] Example 2: The difference from Example 1 is that in the isolation membrane, the molecular weight of PVDF in the first adhesive layer is greater than the molecular weight of PVDF in the second adhesive layer, as shown in Table 1. Except for the differences shown in Table 1, the other conditions are the same as those of Example 1.

[0112] Comparative Example 1: The difference from Example 1 is that in the isolation film, the thickness of the first adhesive layer is substantially equal to the thickness of the second adhesive layer (the thickness of the first adhesive layer is measured to be 1167 nm, and the thickness of the second adhesive layer is measured to be 1180 nm), as shown in Table 1. Except for the differences shown in Table 1, the other conditions are the same as those of Example 1.

[0113] In each embodiment and comparative example, the thickness H of the first adhesive layer in the isolation film is 301 , the thickness of the second adhesive layer H 302 , the molecular weight of PVDF in the first adhesive layer and the second adhesive layer, the peeling force F1 between the separator and the positive electrode sheet, the peeling force F2 between the separator and the negative electrode sheet, the thickness H of the positive electrode coating in the positive electrode sheet 101 , the thickness of the negative electrode coating in the negative electrode sheet H 201 See Table 1.

[0114] In addition, the capacity retention rate of the battery of each embodiment and comparative example after 1000 cycles was measured, and the results are shown in Table 1. Among them, the capacity retention rate test process is as follows: at 25°C, the battery is charged to the upper limit voltage at a rate of 1C, the charging is stopped at 0.05C, and after standing for 30 minutes, it is discharged to the lower limit voltage at a rate of 1C, and stood for 30 minutes; according to this process, the battery is cycled for more than 1000 cycles, and the capacity retention rate of the battery after 1000 cycles is measured (the capacity retention rate of 1000 cycles = the ratio of the capacity of 1000 cycles to the capacity of the first cycle (first cycle)). Among them, the cycle curves (the relationship curve between the capacity retention rate (Capacity ratio) and the number of cycles (Cycling NO.)) of Example 1 and Comparative Example 1 are as shown in Figure 1. Figure 5 shown.

[0115] Table 1

[0116]

[0117] It can be seen from Table 1 that, compared with Comparative Example 1, Example 1 and Example 2 can effectively improve the cycle performance of the battery.

[0118] In addition, in the core stacks of Example 1 and Comparative Example 1, the positive electrode sheets are 32 layers, the negative electrode sheets are 33 layers, and the isolation layers formed by folding the isolation films are 66 layers. The thickness of the core stack of Comparative Example 1 is measured to be 9.71 mm, and the thickness of the core stack of Example 1 is 9.68 mm (Example 2 is basically the same as Example 1). It can be seen that the change in the thickness of the first adhesive layer and the second adhesive layer in Example 1 has little effect on the overall thickness of the core stack.

[0119] In addition, the residual liquid amount of the battery cell of each embodiment and comparative example is measured respectively according to the following process: in the preparation process of the battery, after the battery cell is encapsulated with an aluminum-plastic film (the electrolyte has not been injected at this time), the encapsulated battery cell is weighed, and its mass is m1; then the electrolyte is injected therein, and aging, formation and secondary sealing are carried out. In the secondary sealing process, the electrolyte not absorbed by the battery cell is sucked out, and then the excess aluminum-plastic film is cut off, the mass of the cut aluminum-plastic film is m3, and the mass of the battery after the excess aluminum-plastic film is cut off is m2; the residual liquid amount n of the battery cell is calculated according to n=m2+m3-m1.

[0120] After testing, the residual liquid amount of the battery cell of Example 1 is 125.528g (Example 2 is basically the same as Example 1), and the residual liquid amount of the battery cell of Comparative Example 1 is 122.29g. It can be seen that, relative to Comparative Example 1, after testing, the residual liquid amount of the battery cell of Example 1 is 125.528g (Example 2 is basically the same as Example 1), and the residual liquid amount of the battery cell of Comparative Example 1 is 122.29g. Compared with Comparative Example 1, the battery cells of Examples 1 and 2 have higher electrolyte absorption effect, show better electrolyte wettability, and are beneficial to improving the cycle performance of the battery.

[0121] In addition, although the thickness of the second adhesive layer is reduced to a great extent in Examples 1 and 2 compared with Comparative Example 1, the battery cells of Examples 1 and 2 can still maintain a high hardness, and there is no phenomenon of battery cell softening or collapse of the battery cell ends.

[0122] Taking Example 1 as an example, Figure 3 A is a schematic diagram of the structure of the battery cell of Example 1 supported by the support structure 5. It can be seen that the battery cell of Example 1 is basically free of end collapse, indicating that the battery cell has a relatively high hardness.

[0123] also, Figure 4A is a schematic diagram of the interface structure between the positive electrode sheet and the isolation membrane of Example 1. The surface of the positive electrode coating facing the isolation membrane is uneven, that is, a plurality of first recessed areas are formed on the surface of the positive electrode sheet facing the isolation membrane. The thickness of the first adhesive layer of the isolation membrane of Example 1 is not less than 800nm, so that there is sufficient adhesive between the isolation membrane and the positive electrode sheet. The first adhesive layer basically fills the first recessed area on the surface of the positive electrode coating, so that the positive electrode sheet and the isolation membrane have greater adhesion, thereby avoiding the softening of the battery cell.

[0124] Studies have shown that when the thickness of the first adhesive layer is less than 800nm, the amount of adhesive between the positive electrode sheet and the separator in the prepared battery cell is likely to be insufficient, that is, the first adhesive layer cannot fully fill the first concave area on the surface of the positive electrode coating (the interface structure between the positive electrode sheet and the separator is as shown in FIG. Figure 4 As shown in B), the battery cell is prone to softening (such as Figure 3 As shown in B, the end of the battery cell collapses).

[0125] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the utility model, rather than to limit it. Although the utility model has been described in detail with reference to the aforementioned embodiments, ordinary technicians in this field should understand that they can still modify the technical solutions recorded in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solution deviate from the scope of the technical solution of the embodiments of the utility model.

Claims

1. A battery, characterized in that: include: A first pole piece including a first coating; A second pole piece, comprising a second coating, wherein the thickness of the first coating is greater than the thickness of the second coating; An isolation film is located between the first pole piece and the second pole piece, and the isolation film includes a substrate layer, a first adhesive layer connected to the first coating layer, and a second adhesive layer connected to the second coating layer, wherein the thickness of the first adhesive layer is greater than the thickness of the second adhesive layer.

2. The battery according to claim 1, characterized in that The ratio of the thickness of the first adhesive layer to the thickness of the second adhesive layer is 1.8 to 3.5; And / or, the thickness of the first adhesive layer is 800nm ​​to 1300nm; And / or, the thickness of the second adhesive layer is 300nm-700nm.

3. The battery according to claim 1, characterized in that The ratio of the thickness of the first coating layer to the thickness of the second coating layer is (1.5-3):

1.

4. The battery according to any one of claims 1 to 3, characterized in that: The thickness of the first adhesive layer H 301 The thickness of the first coating H 101 Satisfaction: H 301 =800+a×(H 101 -72), 120≤a≤130, wherein the thickness H of the first adhesive layer 301 The unit is nm, the thickness H of the first coating 101 The unit is μm; And / or, the thickness H of the second adhesive layer is 302 The thickness of the first coating H 101 Satisfaction: H 302 =300+b×(H 101 -72), 95≤b≤105, wherein the thickness of the second adhesive layer H 302 The unit is nm, the thickness H of the first coating 101 The unit is μm; And / or, the thickness H of the first coating layer 101 and the surface density of the first coating ρ 101 Satisfy 0.4≤H 101 / ρ 101 ≤0.5, wherein the thickness H of the first coating 101 The unit is μm, the surface density ρ of the first coating 101 The unit is g / m 2 count; and / or, the thickness of the first coating is 72 μm to 76 μm; And / or, the surface density of the first coating is 161-170 g / m 2 .

5. The battery according to any one of claims 1 to 3, characterized in that: The peeling force between the first pole piece and the isolation film is greater than the peeling force between the second pole piece and the isolation film; Preferably, the peeling force F1 between the first pole piece and the isolation film, and the peeling force F2 between the second pole piece and the isolation film satisfy: 1N / m<F1 / F2≤6N / m; Preferably, the peeling force F1 between the first pole piece and the isolation film satisfies: 6N / m<F1<14N / m; Preferably, the peeling force F2 between the second pole piece and the isolation film satisfies: 2.5 N / m≤F2≤5 N / m.

6. The battery according to any one of claims 1 to 3, characterized in that: The surface of the first coating layer facing the isolation film includes a first recessed area, and the first adhesive layer fills at least a portion of the first recessed area.

7. The battery according to any one of claims 1 to 3, characterized in that: The surface of the second coating layer facing the isolation film includes a second recessed area, and the second glue layer fills at least a portion of the second recessed area.

8. The battery according to any one of claims 1 to 3, characterized in that: The first pole piece is a positive pole piece, and the second pole piece is a negative pole piece.

9. The battery according to any one of claims 1 to 3, characterized in that: The thickness of the substrate layer is 9 μm to 16 μm.

10. The battery according to any one of claims 1 to 3, characterized in that: The battery comprises a plurality of first pole sheets and a plurality of second pole sheets which are stacked, and the plurality of first pole sheets and the plurality of second pole sheets are arranged alternately, and the first pole sheets and the second pole sheets are separated by the isolation film; Alternatively, in the battery, the first pole piece includes a plurality of first straight portions, and a first bent portion connected between every two adjacent first straight portions, and the second pole piece includes a plurality of second straight portions, and a second bent portion connected between every two adjacent second straight portions, the plurality of first straight portions and the plurality of second straight portions are alternately arranged, and the first straight portions and the second straight portions are separated by the isolation membrane.